Friendship and Socialization in the Days of the Covid-19 Pandemic Crisis: Research Analysis and Suggestions - Diamanti, Konstantina; Barmparousis, Charalampos; Nikolaou , Sousanna-Maria (Journal of Social Science Studies, 2022)
The Covid-19 pandemic, already completing almost two years of its irreversible course of action, has exerted and still exerts significant pressures on the social and economic systems of countries worldwide as well as on human relations. Human friendship and socialization, as key factors of human coexistence and cooperation within a social group, have been hit hard by the strict imposition of measures of distancing and social isolation in order to limit the disease and stop its unexpectedly deadly transmission. The present study focuses on exploring the effects of the Covid-19 pandemic on friendship and socialization of people in the new different social contexts that have developed. In the first stage, our work attempts a review of the research and studies carried out during these two years which investigate the changes that occurred in these two dimensions of human coexistence and cooperation to highlight the way in which young adults experienced the consequences of lockdown.